Exchange rate predictability and dynamic Bayesian learning - Rainer Schüssler; Joscha Beckmann; Gary Koop; Dimitris Korobilis (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper considers how an investor in foreign exchange markets might exploit predictive information in macroeconomic fundamentals by allowing for switching between multivariate time series regression models. These models are chosen to reflect a wide array of established empirical and theoretical stylized facts. In an application involving monthly exchange rates for seven countries, we find that an investor using our methods to dynamically allocate assets achieves significant gains relative to benchmark strategies. In particular, we find strong evidence for fast model switching, with most of the time only a small set of macroeconomic fundamentals being relevant for forecasting.
Keywords: C11; D83; F31; G12; G15; G17; 330; Exchange rates; economic fundamentals; Bayesian vector autoregression; forecasting; dynamic portfolio allocation